The Employee Engagement Scale: Initial Evidence for Construct Validity and Implications for Theory and Practice - Shuck, Brad; Adelson, Jill L.; Reio, Thomas G. (Human Resource Management, 2017)
Interest in the employee engagement construct has gained increasing attention in recent years. Measurement tools focused on nuanced areas of engagement (i.e., job engagement and organizational engagement) have been offered; however, no measure of employee engagement has been advanced despite persistent calls in the research. We present the development, method, and results of a three‐dimensional employee engagement measurement tool developed for use in the human resource and management fields of study. Across four independent studies, the employee engagement scale (EES) was found to consist of three subfactors (cognitive, emotional, and behavioral) and a higher‐order factor (employee engagement). Across a series of four studies, we explored the factor structure and reliability of the EES (Study 1), then refined the scale, confirmed the factor structure, and examined reliability and both convergent and nomological validity evidence (Study 2). Next (Study 3), we completed a final reduction in scale items and examined additional evidence of reliability and nomological validity as well as evidence of discriminant validity. Finally (Study 4), we tested for evidence of incremental validity. In the implications for theory and practice section, we discuss the importance of an employee engagement measure aligned alongside an agreed‐upon definition and framework. Limitations and future directions for research—such as the need for further psychometric testing and exploring issues of measurement invariance—are discussed. © 2016 Wiley Periodicals, Inc.